2018
DOI: 10.1021/acs.jpclett.7b03347
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of C/α-MoC and Ag for Efficient Oxygen Reduction Reaction

Abstract: It remains challenging to prepare highly active and stable catalysts from earth-abundant elements for the oxygen reduction reaction (ORR). Herein we report a facile method to synthesize cost-effective heterogeneous C/α-MoC/Ag electrocatalysts. Rotating disc electrode (RDE) experiments revealed that the obtained C/α-MoC/Ag exhibited much superior catalytic performance for ORR than that of C/Ag, C/α-MoC, or even the conventional Pt/C. First-principles calculations indicated that the enhanced activity could be at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 58 publications
(107 reference statements)
1
13
0
Order By: Relevance
“…[20] Similarly, Cao et al also indicated that the catalytic activity of Ag/C was effectively enhanced when α-MoC was deposited onto carbon substrate, and the reason was assigned to the homogeneous distribution of ultrafine Ag NPs facilitated by α-MoC. [21] Interestingly, Cheng et al reported that the electron transfer number could be increased from 3 to 4 accompanied with enhanced catalytic activity, when the loading amount of Ag NPs raised from 20 wt.% to 50 wt.%. [22] Xu et al dramatically increased the loading amounts of Ag from 40 wt.% to 392 wt.%, and the H 2 O 2 yield (corresponding to the 2e À ORR pathway) was observed to decline from 15 % to less than 5 %.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[20] Similarly, Cao et al also indicated that the catalytic activity of Ag/C was effectively enhanced when α-MoC was deposited onto carbon substrate, and the reason was assigned to the homogeneous distribution of ultrafine Ag NPs facilitated by α-MoC. [21] Interestingly, Cheng et al reported that the electron transfer number could be increased from 3 to 4 accompanied with enhanced catalytic activity, when the loading amount of Ag NPs raised from 20 wt.% to 50 wt.%. [22] Xu et al dramatically increased the loading amounts of Ag from 40 wt.% to 392 wt.%, and the H 2 O 2 yield (corresponding to the 2e À ORR pathway) was observed to decline from 15 % to less than 5 %.…”
Section: Introductionmentioning
confidence: 98%
“…[17] Jin et al demonstrated that the Ag NPs (2 nm) protected with single-stranded oligonucleotide sequence (ssDNA) exhibited a 3.5e À pathway towards ORR with excellent stability. [21] Interestingly, Cheng et al reported that the electron transfer number could be increased from 3 to 4 accompanied with enhanced catalytic activity, when the loading amount of Ag NPs raised from 20 wt.% to 50 wt.%. [19] Soo et al noticed that the electron transfer number varied from 2 to 4 when nitrogendoped graphene replaced graphene as substrate.…”
Section: Introductionmentioning
confidence: 99%
“…et al synthesized C/α-MoC/Ag ternary heterogeneous electrocatalysts with high ORR performance, and DFT calculations indicated that the introduction of α-MoC can modify the band structure of Ag and enhance the adsorption of oxygen. [27] Recently, some studies have focused on ZrO 2 as ORR catalyst owing to its strong chemical stability and certain ORR activity. [28][29][30] Okamoto investigated the ORR on the surface of ZrO 2 based on first-principles molecular dynamics simulations, it revealed that when H 2 O 2 formed, the bond of H 2 O 2 would spontaneous break and generate OH on ZrO 2 , which efficiently suppressed two-electron pathway and promoted ORR.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this property, coupling with other transition metals may also have a synergistic effect . Furthermore, Many studies have shown that changes in the metal contents, as well as the changes in the surface crystal structures, are also an effect on the catalytic activity . Especially in some studies, it is seen that the crystal structure affects the polarization resistance and oxygen reduction affinity …”
Section: Introductionmentioning
confidence: 99%
“…11,16 Furthermore, Many studies have shown that changes in the metal contents, as well as the changes in the surface crystal structures, are also an effect on the catalytic activity. 15,17 Especially in some studies, it is seen that the crystal structure affects the polarization resistance and oxygen reduction affinity. 18 In this study, FeNi mesh is treated with Ag in two different ways, chemically and electrochemical deposition.…”
Section: Introductionmentioning
confidence: 99%